know the influence of knowledge management on employee performance and company performance in the office of PLN UP3 Tanjungpinang. - Maryati yati ati (MANAJERIAL DAN BISNIS TANJUNGPINANG, 2020)
The purpose of this research is to know the influence of knowledge management on employee performance and company performance in the office of PLN UP3 Tanjungpinang. This research uses the primary data obtained from the results of the respondent's response to the questionnaire that has been disseminated. This research also uses secondary data derived from corporate data. The analytical techniques used are quantitative techniques which include the data quality test process, classical assumption test, regression analysis test, path analysis test, and statistical hypothesis test. The results showed that knowledge management of employees ' performance was obtained by the value of Tcount 6.188 > Ttable 1.671 and the value of significance is 0.000 < 0.05, then H1 accepted and H0 rejected. Knowledge management of employees performance is obtained by the value of Tcount 2.152 > Ttable 1.671 and significance value is 0036 < 0.05, then H2 accepted and H0 rejected. Performance of employees against the company's performance are obtained Tcount 2.038 value > Ttable 1.671 and value of significance is 0046 < 0.05, then the H3 is accepted and H0 rejected. In conclusion, knowledge management has positive and significant effect on employee performance and company performance. Keywords : Knowledge management, employee performance, company performance.